MEM_UA_2 - Błaszczyk, Mateusz; Pieńkowski, Piotr; Felińska, Małgorzata
The research materials are the diaries of Polish and Ukrainian students. At the end of April 2022, a team of Ukrainian and Polish researchers asked students to prepare written memoirs, the narrative of which was to cover the time from the beginning of the war (i.e., from 24.02.2022) until the reconstruction of the memoirs (the second half of May 2022). At Lviv University, the research invitation was offered during university classes. At the University of Wroclaw, information about the research was disseminated by a student's club. Memories were collected until the end of May 2022. They were sent in text files.In Ukraine, we received 15 memoirs prepared by 12 women and 3 men aged 18-22. In Poland, we had 11 stories prepared by 8 women and 3 men aged 20-25. The studies were prepared in their native language (Ukrainian and Polish).
Keywords: diary; memoirs; war; experience; biographical research; Poland; Ukraine